The Literary Environment as a Component of the Early Childhood Learning Ecosystem - Vina Indriani; Avanti Vera Risti Pramudyani; Dwi Hastuti (Universitas Pendidikan Ganesha, 2026)
Referring to the results of the Indonesian Reading Literacy Activity Index (Alibaca), Indonesia ranks low at 23.09% in terms of literacy access, which affects the PISA results that declined from 2018 to 2022. This condition emphasizes the importance of early intervention through the creation of a literate environment as a means to naturally and enjoyably stimulate children's reading interest. This research aims to explore the literate environment ecosystem for children aged 4-6 years. This study uses a case study approach. Primary data was collected through observations and interviews, and secondary data was collected through documentation. Informants consisted of the school principal and three class teachers. stages of data collection, data display, data reduction, data categorization, and construction. The research results show that providing reading corners, library corners, and literacy-based play areas contributes positively to children's literacy skills. Still, it needs to be revisited and aligned with the concept of a literate environment. The researchers found that teachers do not understand that the cover of a book plays a vital role in literacy. The research implies that literacy can shape character. The study's novelty emphasizes the importance of theme selection, age appropriateness, and covers. It is hoped that the books used for literacy are well-maintained and enriched with themes.